Educação do campo: concepções e teorias contra hegemônica - CARMO, Eraldo Souza do (Universidade Federal do Pará, 2021)
This article aims to discuss the theoretical principles of the Movement's struggle On A Field of Education as proposed against hegemonic facing education to the capitalist state. The analysis was from a literature review in order to confront the premises of this movement advocating an educational project that takes into account the characteristics and realities of the subjects of the field. However, there are conflicting processes, since the educational policies are the assumptions of the capitalist state, where education takes the perspective merchandise. Still, it is evident that despite the contradictions, the movement has made consistent propositions and managed to include in the government bases its social demands. However, the embodiment does not always answer your prospects.